Al-Maturidi and the development of Sunni theology in Samarqand - Rudolph, Ulrich; Adem, Rodrigo (Leiden, Netherlands : Brill, 2015)
Al-Maturidi (d. 944 CE), the prominent Hanafi scholar from Samarqand, succeeded in formulating a theological doctrine which is widely accepted in Sunni Islam to this day. The present volume which is a revised English version of the German original published in 1997 examines his teachings by describing their principal characteristics and situating them in the history of kalam.Part one investigates the development of Hanafi thought in Transoxania before Maturidi's time. Part two deals with the other religious groups (in particular the Mu'tazilites) which emerged in this area during his lifetime. Part three shows how he explained and defended the position of his predecessors; in doing so, he reformed their traditional views, thereby developing his own theology which then became the basis of a new tradition, viz. the Maturidite school.
Prefacep. ixList of Abbreviationsp. xIntroductionp. 11 The Famous Unknownp. 12 The First Image: al-Maturidi as Faithful Successor to Abu Hanifap. 43 The Second Image: al-Maturidi as Eastern Counterpart to al-Ash'arip. 74 The State of Research and Current Conceptualizationsp. 11Part 1Preliminary History and Conditions: The Hanafite Tradition in Northeastern Iran1 The Foundation and Establishment of Hanafite Theology in the Second/ Eighth and Early Third/Ninth Centuriesp. 231.1 The Preparatory Role of the Murji'ap. 231.2 Abu Hanifa (d. 150/767) and the Letters to'Uthman al-Battlp. 281.2.1 The First Risalap. 281.2.2 The Second Risalap. 361.3 Abu Muqatil al-Samarqandi (d. 208/823) and the Kitab al-'Alim wa-l-muta'atlimp. 421.4 Abu Muti al-Balkhi (d. 199/814) and the Kitab al-Fiqh al-absatp. 532 Development in the Third/Ninth Centuryp. 722.1 Stagnation in Theology and a Lack of Sources: Abu Bakr al-Samarqandi (d. 268/881-2)p. 722.2 Hanafite Elements in Ibn Karram's Theology (d. 255/869)p. 753 The State of Theology during al-Maturidi's Lifetimep. 813.1 Abu Muti Makhul al-Nasafi (d. 318/930) and the Kitab al-Radd'ala ahl al-bida' wa-l-ahwa'p. 813.2 Al-Hakim al-Samarqandi (d. 342/953) and the Kitab al-Sawdd al-a'zamp. 97Part 2The Emergence of al-Maturidi4 Life and Activityp. 1254.1 Biographical Reportsp. 1254.2 Teachersp. 1324.2.1 Abu Bakr al-Juzjanip. 1324.2.2 Abu Nasr al-'Iyadip. 1344.3 Studentsp. 1374.3.1 Abu Ahmad al-'Iyddip. 1374.3.2 Abu l-Hasan al-Rustughfanip. 1404.3.3 'Abd at-Karim al-Pazdawlp. 1445 Theological Opponentsp. 1485 The Wide Spectrum of Polemicp. 1485.2 The Mu'tazilite Challengep. 1565.2.1 Abu l-Qasim al-Balkhi al-Ka'bi and the Baghdad Schoolp. 1585.2.2 The Basran Schoolp. 1595.2.3 Ibn al-Rawandip. 1605.2.4 Muhammad b. Shahibp. 1625.3 The Hanafite Rivals: al-Najjar and the School of Rayyp. 1635.4 The Focal Point of the Discussion: Refutation of the Dualists and the'Dahriya'p. 1666 Worksp. 1806.1 Lost Worksp. 1806.2 Extant Textsp. 1836.2.1 The Ta'wilat al-Quran or Ta'wilat ahl al-sunnap. 1836.2.2 The Kitab al-Tawhidp. 189Part 3Al-Maturidi's Theology7 Structures and Their Forerunning Modelsp. 2017.1 The Structure of the Kitah at-Tawhidp. 2017.2 The Bipartite Nature of the Workp. 2147.3 Possible Sourcesp. 2238 An Outline of al-Maturidi's Teachingsp. 231 Prolegomena: Epistemologyp. 2318.1 The Worldp. 2338.1.1 The Contingency of the Worldp. 2338.1.1.1 Al-Maturidi's Proofsp. 2338.1.2 The Background of the Argumentp. 2368.1.2 The Ontological Structure of the Worldp. 2428.1.2.1 Bodies and Accidentsp. 2428.1.2.2 Naturesp. 2538.1.2.3 Informing Factors and Exemplary Modelsp. 2608.2 Godp. 2628.2.1 God's Existencep. 2628.2.2 God's Knowabilityp. 2648.2.2.1 The Rationalistic Position of the Hanafitesp. 2648.2.2.2 Inferring the Unseen from that which is Seenp. 2668.2.3 God's Onenessp. 2688.2.4 The Otherness of the Onep. 2748.2.5 God's Attributesp. 2788.2.5.1 Earlier Hanafite Viewsp. 2788.2.5.2 Al-Maturidi's Contributionp. 2828.2.6 The Ambiguous Descriptions of God in the Qur'anp. 2878.2.6.1 Earlier Hanafite Viewsp. 2878.2.6.2 Al-Maturidi's Contributionp. 2918.2.7 God's Wisdomp. 2968.3 Human Beingsp. 3008.3.1 Human Rationalityp. 3008.3.2 Human Actionsp. 3028.3.2.1 The Conceptualization of the Hanafites and the Karramitesp. 3028.3.2.2 Al-Maturidi's Contributionp. 3048.3.3 Belief and Sinp. 308Concluding Observationsp. 3131 Al-Maturidi's Position in Islamic Theologyp. 3132 The Relationship to Abu Hanifap. 3173 The Relationship to al-Ash'arip. 3174 The Formation of the Maturidiyap. 319Appendix: Inauthentic and Doubtful Textsp. 3251 Inauthentic Textsp. 3251.1 Sharh al-Fiqh al-akbarp. 3251.2 Risala fi l-'aqa'idp. 3291.3 Kitab al-Tawhidp. 3291.4 Risala fi-ma la yajuz al-waqf'alayhip. 3292 Doubtful Textsp. 330Fawa'idp. 330Bibliographyp. 332Index of Peoplep. 349Index of Religious and Political Movementsp. 353Index of Arabic Termsp. 355
Includes bibliographical references and indexes.
Translated from German.
Keywords: Maturidi Muhammad ibn Muhammad, -- -944 or 945.; Islam -- Doctrines -- History; Islam -- Uzbekistan -- Samarqand -- History; Maturidiyah